2013
DOI: 10.1007/s12264-013-1310-6
|View full text |Cite
|
Sign up to set email alerts
|

One hour of pilocarpine-induced status epilepticus is sufficient to develop chronic epilepsy in mice, and is associated with mossy fiber sprouting but not neuronal death

Abstract: Determining the minimal duration of status epilepticus (SE) that leads to the development of subsequent spontaneous seizures (i.e., epilepsy) is important, because it provides a critical time-window for seizure intervention and epilepsy prevention. In the present study, male ICR (Imprinting Control Region) mice were injected with pilocarpine to induce acute seizures. SE was terminated by diazepam at 10 min, 30 min, 1 h, 2 h and 4 h after seizure onset. Spontaneous seizures occurred in the 1, 2 and 4 h SE group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…In man, mortality is high during refractory SE that requires general anesthesia (32,33), and the 30-day mortality is ~35% in adults who experience at least an hour of SE (34). Mortality is also encountered in rodents experiencing SE, and mortality rate is positively correlated with time spent in SE (35). We found no role for myeloid cell EP2 or neuronal EP2 in acute mortality during SE.…”
Section: Se Results In the Rapid Induction Of Numerous Inflammatory Cmentioning
confidence: 67%
“…In man, mortality is high during refractory SE that requires general anesthesia (32,33), and the 30-day mortality is ~35% in adults who experience at least an hour of SE (34). Mortality is also encountered in rodents experiencing SE, and mortality rate is positively correlated with time spent in SE (35). We found no role for myeloid cell EP2 or neuronal EP2 in acute mortality during SE.…”
Section: Se Results In the Rapid Induction Of Numerous Inflammatory Cmentioning
confidence: 67%
“…All behavioral experiments were conducted the next day after 4 weeks of daily rapamycin treatment. Morris water maze was conducted as described previously [ 13 ]. Briefly, a platform of 10 cm in diameter was submerged 1 cm beneath the surface and located at a fixed position and remained constant throughout the training period.…”
Section: Methodsmentioning
confidence: 99%
“…Lithium was intraperitoneally injected to rats (100 mg/ml), and pilocarpine was intraperitoneally injected (10 mg/ml) after 18-20 h [3]. Epilepsy intensity scoring was performed according to Racine graded standard [23].…”
Section: Induced Epilepsymentioning
confidence: 99%
“…Preclinical studies demonstrated that accumbens nucleus shell (ACbSh) had been involved in the progress of epilepsy. Pilocarpine-induced rat epilepsy models showed that hippocampus had severe degeneration of neurons, while multiple nucleus in thalamus and ACbSh had also suffered from neuronal degeneration [3,23]. However, details were not clear as to the association between ACbSh and epilepsy.…”
Section: Introductionmentioning
confidence: 99%